A modern Maistre : the social and political thought of Joseph de Maistre - Bradley, Owen, 1960- (European horizons., 1999)
"A Modern Maistre provides the first general account of the social and political thought of Joseph de Maistre (1753-1821), a founding author of Continental conservative philosophy. Commonly repudiated or ignored as an inconsistent and retrograde extremist, Maistre emerges on closer consideration as a subtle social theorist and a shaping force in modern intellectual history. Through his decisive effect upon Comte and Baudelaire, Maistre's influence far exceeds the narrow conservatism with which he is usually associated. Indeed, his critique of the Enlightenment bears an uncanny resemblance to central claims of postmodernist thought."--Jacket